(untitled) (Research, Society and Development, 2022)
This article aims to analyze the importance of digital literacy in the training of teachers in the teaching-learning process. Therefore, we carried out a bibliographical, exploratory-descriptive research. We observed that the new literacies movement is based on critical pedagogy and philosophical foundations of critical literacy and pedagogical recommendations, inserting new technologies. Therefore, the continuing education of the teacher implies the change of the teacher himself and of the teaching institution in which he works, since it allows the realization of innovative and successful experiences in the educational context. Teachers need to be aware of the discursive genres and digital languages ​​used by students, in order to connect creatively and constructively to the school day-to-day, which is essential. It is concluded that the teacher has a role to play in this reinvention of forms of teaching, learning and innovation. The intelligent use of digital information and communication technologies (DICTs) is not an inherent attribute, but it is linked to the way in which the task in which it will be used is conceived, as a tool in teaching and learning in an effective and satisfactory way, since digital literacy is necessary and short importance.